Embracing the tension: managing short-term horizons in long-term transitions - Claire Beach; Sitong Michelle Chen; Michael SW Lee; Richard Starr (Research in Hospitality Management)
The future of hospitality management necessitates achieving economic, environmental and social sustainability simultaneously, leading to inherent tensions in sustainability. Guided by paradox theory, this article explores how accommodation providers can embrace intertemporal tensions to fulfil short-term operational demands while advancing long-term sustainable transitions. The conceptual model presented in this article highlights the iterative and non-linear nature of sustainable transitions, outlining five key steps for implementation: measuring and reporting sustainability metrics; embedding sustainable practices within the firm; collaborating with partners; advocating for industry and social change; and re-evaluating progress. This article refines these steps using five in-depth case studies on accommodation providers in New Zealand. The data, consisting of semi-structured interviews and observations, is then analysed using applied thematic analysis, revealing actionable strategies for managing the intertemporal tensions that arise during sustainable transitions. This study highlights the centrality of intertemporal tensions in sustainable transitions and provides practical guidance to help managers to embrace intertemporal tensions while implementing sustainable transitions. By implementing these strategies, accommodation providers can embrace intertemporal tensions, effectively balancing immediate objectives with long-term commitments, driving meaningful change towards a more sustainable future in hospitality management.